2020
DOI: 10.3892/etm.2020.8787
|View full text |Cite
|
Sign up to set email alerts
|

Comparing post‑operative analgesic effects of varying doses of dexmedetomidine as an adjuvant to ropivacaine for ultrasound‑guided dual transversus abdominis plane block following laparotomy for gynecologic malignancies

Abstract: The aim of the present study was to determine the analgesic effects of ropivacaine combined with different doses of dexmedetomidine for ultrasound-guided transversus abdominis plane (TAP) block immediately following laparotomy in patients with gynecologic malignancies. A further aim was to determine the appropriate clinical dose of dexmedetomidine as an adjuvant for ropivacaine. Patients with gynecologic malignancies scheduled for laparotomy were randomly assigned to group R (TAP block with 0.3% ropivacaine), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 41 Studies of DEX-assisted nerve blocks have shown that 0.5–2 g/kg DEX combined with 0.3% ropivacaine applied with TAP block is a safe and effective analgesic treatment in gynecological surgery. 42 …”
Section: Discussionmentioning
confidence: 99%
“… 41 Studies of DEX-assisted nerve blocks have shown that 0.5–2 g/kg DEX combined with 0.3% ropivacaine applied with TAP block is a safe and effective analgesic treatment in gynecological surgery. 42 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to kidney transplantation and Caesarean section, dexmedetomidine has been successfully applied as an adjuvant in hernia repair Madangopal et al 87 open treatment of gynecological malignant tumor, 88 minimally invasive colorectal surgery, 161 laparoscopic cholecystectomy, 89 laparoscopic bile duct exploration in children 90 and other operations. It has obvious advantages in postoperative analgesia.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…Dex has been used in the perioperative period of gynecological malignancy surgery [5], laparoscopic hepatobiliary surgery [6], and thyroid surgery [7]. It has been proposed that preoperative administration of 0.8 μg/(kg • h) Dex is superior to 0.4 μg/(kg • h) [8].…”
Section: Introductionmentioning
confidence: 99%